Compliance as an Alternative Instrument for the Protection of Human Rights and the Ineffectiveness of Decree No. 9.571/2018 - Adamatti, Bianka; Ferreira, Eduardo Adolfo (Journal of Law and Corruption Review, 2023)
With the advancement of globalisation, economic and technological processes, and the disruption of obsolete social standards, it is no longer acceptable for corporations to seek their development and profits without observing the pertinent aspects of the human condition, which have their guiding principles established by the United Nations Human Rights Council. Thus, in order to encourage the adoption of good practices in Human Rights by national and multinational companies, the Decree No. 9.571/2018 established the guidelines for implementing Human Rights Compliance programmes in organisations. This study analyses Decree No. 9.571/2018 and demonstrates the importance of implementing Human Rights Compliance programmes, which, in addition to providing protection and encouragement to Human Rights in the corporate-business environment, may positively influence the results and reputation of businesses in the market. While some companies are adopting Human Rights policies, from a Corporate Social Responsibility perspective, the decree under analysis is optional and does not provide an incentive for companies to implement Human Rights Compliance programmes, resulting in a guideline without practical effectiveness.